(untitled) (TEST XY. Rassegna critica di studi sulla rappresentazione dell’architettura e sull’uso dell’immagine nella scienza e nell’arte, 2018)
The ubiquitous nature of lettering and typography in Irish towns and cities offers a representation of both visual landscape and cultural heritage. These marks and glyphs, both analogue and digital as they appear contextualised in their environment become semantic guides and cultural signifiers informing identity and place. Geographically located one hundred miles apart and politically situated in different states, Belfast and Dublin, however, share a rich varied socio–culture heritage. This research interacts with and comments on this shared culture and the vernacular in an attempt to examine and identify typographic nuances and idiosyncrasies. This is achieved through the mapping and re–contextualising of the typographic environment along the one hundred mile arterial route, making reference to 26 points/locations. Our methodology investigates the various ways in which place and identity can be acknowledged, quantified and analysed through lettering and typography. It explores intrinsic accidental and intentional typographic markers–inter alia, shop signs, way finding, ghost lettering, graphical interfaces, train stations and religious markers.